2007
DOI: 10.4141/s06-055
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-release urea for winter wheat in southern Alberta

Abstract: . Controlled-release urea for winter wheat in southern Alberta. Can. J. Soil Sci. 87: 85-91. The recent development of low-cost controlled-release urea (CRU) may provide additional options for N fertilization of winter wheat (Triticum aestivum L.). Two field experiments were conducted over 3 yr at three locations in southern Alberta to evaluate different options of applying CRU to winter wheat. In the first experiment, three N fertilizers (20-day CRU, 40-day CRU and urea) were seed-placed and side-banded at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 11 publications
6
39
0
Order By: Relevance
“…Notably, CRU was applied with the seed about 6 months prior to the GSP spring broadcast urea application in 2013. The placement and timing of the CRU AMP and urea GSP were not the same because fall-applied urea was not a standard practice (due to shallow gravel contact) and CRU can release too slowly to benefit wheat if spring broadcast in the NGP (McKenzie et al 2007). The split application may not have been effective at reducing leaching in 2013 because on Field C the second application was completed on 23 May, immediately prior to 180 mm of precipitation in the next 12 days, enough to move substantial UAN below the root zone before it could be used by the crop.…”
Section: Nitrate Leaching Resultsmentioning
confidence: 99%
“…Notably, CRU was applied with the seed about 6 months prior to the GSP spring broadcast urea application in 2013. The placement and timing of the CRU AMP and urea GSP were not the same because fall-applied urea was not a standard practice (due to shallow gravel contact) and CRU can release too slowly to benefit wheat if spring broadcast in the NGP (McKenzie et al 2007). The split application may not have been effective at reducing leaching in 2013 because on Field C the second application was completed on 23 May, immediately prior to 180 mm of precipitation in the next 12 days, enough to move substantial UAN below the root zone before it could be used by the crop.…”
Section: Nitrate Leaching Resultsmentioning
confidence: 99%
“…However, in studies comparing urea and PCU applied at seeding for winter wheat, grain yield and protein concentration were similar as long as there was sufficient separation between the seed and applied urea (Middleton et al 2004;McKenzie et al 2007;Irvine et al 2010). The similar efficacy of PCU and urea in these studies was possibly due to relatively dry conditions and negligible over-winter N loss.…”
mentioning
confidence: 81%
“…In more humid regions of the prairies, spring broadcast ammonium nitrate was generally more effective than fall N application due to the greater risk of over-winter N loss (Grant et al 1985;Fowler and Brydon 1989a, b;Campbell et al 1991;Johnston and Fowler 1991a, b). For spring broadcast application, urea was less effective than ammonium nitrate in three of nine trials in a study by Fowler and Brydon (1989a), but equally effective in other studies (Campbell et al 1991;Middleton et al 2004;McKenzie et al 2007;Irvine et al 2010), despite the potential for volatilization losses of ammonia from broadcast urea (Harrison and Webb 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have observed that coated urea increased the yields of wheat (Fan et al 2004), barley and potato (Shoji et al 2001), and onion (Drost et al 2002), and nutrient use efficiency (Shoji et al 2001), but had no effect on the protein content of wheat (Peltonen and Virtanen 1994). In southern Alberta, coated and uncoated urea produced no significant differences in the seed yield and N uptake of winter wheat (McKenzie et al 2007). These divergent experimental results suggest that: (i) CRU vary greatly in their effectiveness with field conditions, i.e., may not be beneficial under some field conditions, e.g., dry soil in southern Alberta; and (ii) some forms of CRU and its placement method may not effectively synchronize N release with crop demand.…”
mentioning
confidence: 99%